Children's concept of family among nuclear and single-parent families - Del Mundo, Ana Karolina A.
This study focused on the children's concept of family among nuclear and single-parent families. The respondents of the study were 20 five-year-old preschool children from the U.P. Child Development Center (CDC) and the Parish of the Holy Sacrifice Outreach Program (PHSOP). Half of the respondents were from nuclear families and half from single-parent families. An interview schedule of children and a parent survey were used to gather data. For the interview schedule, the children respondents were also asked to draw their concept of as family in addition to personal interview. Responses were analyzed using in-depth analysis and descriptive statistics. The findings of the study showed the respondents' concept of family is divided into two categories: cognitive and effective. Part of the cognitive aspect is the family composition and family practices. On the other hand, the effective aspect is composed of the children's fondness and feelings towards their families. There is no major difference on the children's concept of family from the two family structures, except for the subcategories made for each category. Based on the data, it shows that the time spent with the family, friends, other relatives, affection towards and from the family, and the things the family does together are significant to the children. These contribute mainly to the child's concept of a family.